ASPEK PSIKOLOGIS TOKOH UTAMA DALAM NOVEL SAGAGANG JACARANDA KARYA RISNAWATI: KAJIAN STRUKTURAL DAN PSIKOLOGI - Rima Mawar Wati; Dedi Koswara; Retty Isnendes (HUMAN: Journal of Social Humanities and Science, 2026)
This study aims to describe the psychological aspects of the main character in the novel Sagagang Jacaranda by Risnawati, utilizing Sigmund Freud's theory of literary psychology. A qualitative descriptive method was employed, utilizing reading and note-taking techniques to outline the story's structural elements and the main character's psychological aspects. The study's findings cover two areas: first, the structural elements contained within the novel—specifically theme, characters, plot, setting, and message. The novel's theme centers on an individual's internal conflict in accepting an unexpected reality. The protagonist is Adis, while the antagonists are Mamih and Gagah’s father (Papih). The plot is mixed (non-linear), featuring 20 temporal settings, 36 spatial settings, and one social setting. Second, regarding the psychological aspects of the character Adis, the Superego emerges as the dominant force, reflecting a personality that is mature, responsible, and capable of self-control when facing various life conflicts. Nevertheless, the Id remains present as an instinctive drive influencing the character's desires and emotions through subconscious reflex responses, though its intensity does not surpass the dominance of the Superego. Meanwhile, the Ego acts as a mediator, helping Adis balance Id-driven impulses with the reality she faces; consequently, her decisions and actions remain rational and take the interests of others into account. Thus, the balance between the Id, Ego, and Superego shapes Adis into a character who not only seeks to fulfill personal desires but also upholds moral and ethical values ​​in every decision-making process.